The Use of Literature in English as a Foreign Language Teaching and Learning Process: The Relationship and Suggested Techniques to be Used in EFL Classrooms - Herminus Efrando Pabur; Ismail ,; Muhammad Ilham Ali; Devilito Prasetyo Tatipang (Edumaspul: Jurnal Pendidikan, 2023)
Literature, in a broad definition, can be defined as a term that denotes works such as drama, poetry, novel, and short story. From an educational point of view, literature can be utilized as a medium for teaching English as a foreign language. This study attempts to suggest the activities that can be used to maximize the prominent role of literature in teaching English skills and describe the relationship between literature and the English teaching and learning process. This study employs the qualitative approach with a library research technique. The data are collected from books and articles in various academic journals. The findings show that the relationship between literature and English teaching and learning is symbiotic and inseparable. Literature does have a really important role in teaching English as a foreign language: literature can be used in developing students’ language skills: listening, speaking, reading, and writing. However, the use of literature in English classes can be fully optimized when accurate methods or techniques are used. This study suggests that the use of literature to enhance students’ language skills has to be done in integration.